DAMPAK KEBIJAKAN DESENTRALISASI FISKAL TERHADAP TRANSFORMASI EKONOMI DI PROVINSI JAWA BARAT - Arief Dirgantoro, Muhammad; Mangkuprawira, S; Siregar, H; Sinaga, B.M (LPPM Universitas Terbuka, 2009)
The objectives of this research are : (1) to analyze structural economic transformation in West Java Province, (2) to analyze linkage inter sector on economic transformation process inter farm, industry and other sectors, (3) to analyze impact of fiscal decentralization to economic growth and structure economic transformation in West Java Province.   In order to answer the above, a simultaneous equity model was established, consisting of 32 structural equities and 15 identity equities. Furthermore, this research used data pooling where data were analyzed with descriptive analysis, econometrics model, as well as predictions using a variety of policy scenario alternatives.  Model was then estimated by 2SLS method with SYSLIN procedures, while prediction simulation was performed by using SIMNLIN procedures.  In its development era, West Java province have done transformation of economy.  During this economy structure transformation process, the decrease on agricultural sector contribution was automatically increase contribution on industry, but it was not increase contribution on other sector.  The increase on local taxes receipt gave positive impact on output growth, and it gave economy structure transformation.  The increase personel current expenditure gave positive impact on agriculture output growth and economic ratio.  The increase development expenditure for agriculture gave positive impact on output growth agriculture and economic ratio, but it gave negative impact on total output growth.  The increase expenditure for infrastructure gave positive impact on output growth, ang it gave economy structure transformation.